2021
DOI: 10.1177/03008916211012760
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for management of patients with lung cancer during COVID-19 in an Italian cancer institute: SmartDoc Project

Abstract: Background: Telemedicine, and particularly video-consulting, has rapidly accelerated since the coronavirus disease 2019 (COVID-19) pandemic outbreak. The role of e-healthcare for the management of patients with lung diseases is evolving. We report the results of the initial experience of the SmartDoc Project, a telemedicine program activated in a cancer center (Istituto Nazionale Tumori) at the epicenter of the COVID-19 pandemic onset in Italy. Method: The SmartDoc project was established to guarantee continui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…It is encouraging to note that in 2021 to date, there has been much investigation of the practicality of telemedicine protocols [e.g. ( 26 28 )]. Findings in this regard appear to be somewhat mixed, with some studies suggesting that most participants were happy to continue telemedicine visits [e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is encouraging to note that in 2021 to date, there has been much investigation of the practicality of telemedicine protocols [e.g. ( 26 28 )]. Findings in this regard appear to be somewhat mixed, with some studies suggesting that most participants were happy to continue telemedicine visits [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Findings in this regard appear to be somewhat mixed, with some studies suggesting that most participants were happy to continue telemedicine visits [e.g. ( 28 )], and others suggesting that most participants prefer in-person visits [e.g. ( 26 )].…”
Section: Discussionmentioning
confidence: 99%
“…The eligibility process applied to the selected references, after the elimination of the duplicated ones, returned 39 works [ 5 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], including a review focused on the relationship between telemedicine and radiotherapy [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study in [ 40 ] reported the evolution of a multidisciplinary center for myocarditis towards a telemedicine system. Important applications are recorded in oncology, such as in breast cancer [ 21 ], lung cancer [ 25 ], connections to the stoma centers [ 29 ], the management of patients with differentiated thyroid cancer [ 39 ], and related radiotherapy applications [ 35 ]. The neurology sector has also recorded an important use of applications in Parkinson’s disease [ 44 ]; in the use of telemedicine for the multidisciplinary assessment of patients with Amyotrophic Lateral Sclerosis [ 47 ]; for multiple sclerosis [ 28 ]; for a headache specialist center; and in applications of telephysiotherapy [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation